2000
DOI: 10.1073/pnas.98.1.295
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic regulation of recurrent excitation by D1 receptors in prefrontal circuits

Abstract: The prefrontal cortex plays a fundamental role in the working memory functions of the cerebral cortex and is also the site of dysfunction in several neurological and psychiatric disorders, including schizophrenia. Prefrontal neurons are distinguished by their capacity for sustained activity during the time a stimulus is held in memory, and this mnemonic response is considered a substrate for a variety of cognitive functions. The neuronal basis for sustained activity in prefrontal neurons is unknown but is thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
98
1
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 198 publications
(115 citation statements)
references
References 36 publications
(18 reference statements)
15
98
1
1
Order By: Relevance
“…Second, D 1 receptor activation attenuates both excitatory responses in the mPFC evoked by local stimulation and BLA-evoked responses in the NAc via a presynaptic mechanism (Floresco et al, 2001;Gao et al, 2001;Seamans et al, 2001a;Charara and Grace, 2003;Mair and Kauer, 2007). Furthermore, we observed a dramatic alteration in the paired-pulse ratio of BLA-evoked firing after VTA stimulation, which suggests a presynaptic mode of action (Fig.…”
Section: Da Modulation Of Bla-evoked Excitationmentioning
confidence: 60%
“…Second, D 1 receptor activation attenuates both excitatory responses in the mPFC evoked by local stimulation and BLA-evoked responses in the NAc via a presynaptic mechanism (Floresco et al, 2001;Gao et al, 2001;Seamans et al, 2001a;Charara and Grace, 2003;Mair and Kauer, 2007). Furthermore, we observed a dramatic alteration in the paired-pulse ratio of BLA-evoked firing after VTA stimulation, which suggests a presynaptic mode of action (Fig.…”
Section: Da Modulation Of Bla-evoked Excitationmentioning
confidence: 60%
“…This is consistent with studies showing that DA acts on D1/D5 receptors to enhance intracortically evoked EPSCs in layer II/III (Gonzalez-Islas and Hablitz, 2003) and layer V pyramidal neurons of rat PFC (Seamans et al, 2001a), without affecting mini-EPSCs (Zhou and Hablitz, 1999), that is, a direct postsynaptic action on the pyramidal neuron. In contrast, studies using paired-neuron stimulation/recordings suggest that D1 receptors may produce an inhibitory response via attenuation of excitatory transmission in the ferret (Gao et al, 2001) and in the primate (with coactivation of D2 receptors, Urban et al, 2002). Although our data do not directly address pre-vs postsynaptic events, the D1 enhancement of the late Figure 9 D4 antagonist administration produces little enhancement of both membrane excitability and short latency-evoked responses in Type I pyramidal neurons in which relatively few axon collaterals were preserved in slices ( Figure 2 a3; b2).…”
Section: Discussionmentioning
confidence: 91%
“…Studies in cats (Huda et al, 2001) and rodents (Awenowicz and Porter, 2002) have demonstrated reduced excitability in motor neurons, which produce the MEP to TMS, after application of DA. A recent study in monkey prefrontal cortex showed that DA decreases horizontal excitatory transmission in cortical layer 5 by a D1 receptormediated mechanism (Gao et al, 2001). Such horizontal excitatory connections in the motor cortex are likely involved in the amplification of excitatory signals that results in the MEP after TMS.…”
Section: Discussionmentioning
confidence: 99%